Emerging COVID-19 variants and their impact on SARS-CoV-2 diagnosis, therapeutics and vaccines - Fernandes, Queenie; Inchakalody, Varghese Philipose; Merhi, Maysaloun; Mestiri, Sarra; Taib, Nassiba; Moustafa Abo El-Ella, Dina; Bedhiafi, Takwa; Raza, Afsheen; Al-Zaidan, Lobna; Mohsen, Mona O.; Yousuf Al-Nesf, Mariam Ali; Hssain, Ali Ait; et al. (Annals of medicine (Helsinki), 2022)
The emergence of novel and evolving variants of SARS-CoV-2 has fostered the need for change in the form of newer and more adaptive diagnostic methods for the detection of SARS-CoV-2 infections. On the other hand, developing rapid and sensitive diagnostic technologies is now more challenging due to emerging variants and varying symptoms exhibited among the infected individuals. In addition to this, vaccines remain the major mainstay of prevention and protection against infection. Novel vaccines and drugs are constantly being developed to unleash an immune response for the robust targeting of SARS-CoV-2 and its associated variants. In this review, we provide an updated perspective on the current challenges posed by the emergence of novel SARS-CoV-2 mutants/variants and the evolution of diagnostic techniques to enable their detection. In addition, we also discuss the development, formulation, working mechanisms, advantages, and drawbacks of some of the most used vaccines/therapeutic drugs and their subsequent immunological impact. Key message The emergence of novel variants of the SARS-CoV-2 in the past couple of months, highlights one of the primary challenges in the diagnostics, treatment, as well as vaccine development against the virus. Advancements in SARS-CoV-2 detection include nucleic acid based, antigen and immuno- assay-based and antibody-based detection methodologies for efficient, robust, and quick testing; while advancements in COVID-19 preventive and therapeutic strategies include novel antiviral and immunomodulatory drugs and SARS-CoV-2 targeted vaccines. The varied COVID-19 vaccine platforms and the immune responses induced by each one of them as well as their ability to battle post-vaccination infections have all been discussed in this review.